Incidence Of Klebsiella Pneumoniae Subsp Pneumoniae In Food And Environmental Samples Isolated From Mysore City, India And Its Antibiogram - LITTY BABU,; HARISHCHANDRA SHRIPATHY MURALI,; HARSH VARDHAN BATRA, (International Journal of Pharma and Bio Sciences, 2015)
Foodborne illnesses are of great concern and serious global threat. There are both human and economical losses worldwide due to consumption of contaminated food and water. K. pneumoniae, a Gram-negative rod shaped bacteria belonging to the family Enterobacteriaceae is responsible for foodborne infections all over the world. Therefore, the aim of our study is to evaluate the incidence of Klebsiella pneumoniae from food and environmental samples in Mysore region. A total of 82 samples were screened for the presence of possible contamination by K. pneumoniae subsp pneumoniae. Among these twenty three (28%) strains were confirmed as K. pneumoniae subsp pneumoniae by MALDI-TOF. The present study revealed a high percentage (53%) of incidence of Klebsiella species from the samples. All the K. pneumoniae subsp pneumoniae were susceptible to all the antibiotics (26) excluding few strains. However, all the tested strains are resistant to ampicillin and all these strains were capable of forming biofilms.